CATATAN KEBERADAAN DAN IDENTIFIKASI JAMUR AGARICOMYCETES DI HUTAN DANAU SITU GEDE BOGOR - Putra, Ivan; Chan, Carey; Qowiyyu Asca, Annisa; Early, Addira; Amana Nousra Atsemani, Jezila; Laila Izzati, Zhofira; Arief Rahman, Muhammad; Fitri Ani, Desi; Aji Mahardhika, Wahyu (Jurnal Biogenerasi, 2024)
Agaricomycetes belong to the group of macrofungi in the Basidiomycota division, which generally form fruiting bodies and reproduce sexually using basidiospores. This group of fungi can be found in terrestrial environments and mostly function as decomposers. Agaricomycetes are commonly found in Indonesia, especially in humid and shaded locations. For example, Situ Gede, a lake located in Dramaga, Bogor, provides a suitable environment for the growth of Agaricomycetes, such as Lycoperdon sp. and Lentinus sp., which are Agaricomycetes that can be found on the ground or decaying wood. However, descriptive data on these two types of fungi have not been widely published. A study was conducted to determine the morphological characteristics and distribution of Lycoperdon sp. and Lentinus sp. found in the forest around Situ Gede lake. The study involved documenting and observing samples morphologically and microscopically in the Biology Department Laboratory of IPB University, Bogor, West Java. The morphological observations revealed that Lycoperdon sp. has a cap and stalk with brownish-white color, brown spots, and gleba containing mature brownish spores, as well as basidiospores and basidiospores on the stalk, as observed under the microscope. Lentinus sp. has a brownish-white cap, brown stalk, yellowish-white gills, septate hyphae, and ellipsoidal basidiospores. This study contributes to documenting the presence of Agaricomycetes fungi in Indonesia and provides a basis for further research on the potential and utilization of these fungi